2016
DOI: 10.1016/j.chiabu.2016.04.005
|View full text |Cite
|
Sign up to set email alerts
|

Sexual harassment victimization in adolescence: Associations with family background

Abstract: Sexual harassment has been studies as a mechanism reproducing inequality between sexes, as gender based discrimination, and more recently, as a public health problem. The role of family-related factors for subjection to sexual harassment in adolescent has been little studied. Our aim was to study the role of socio-demographic family factors and parental involvement in adolescent's persona life for experiences of sexual harassment among 14-18-year-old population girls and boys. An anonymous cross-sectional clas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
66
1
7

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 50 publications
(79 citation statements)
references
References 39 publications
5
66
1
7
Order By: Relevance
“…Many studies have focused on any experiences in a given time frame (American Association of University Women, 2001;Bucchianeri et al, 2014;Chiodo et al, 2009;Petersen & Hyde, 2009) and therefore focusing on experiences that have occurred 'repeatedly' obviously results in smaller numbers. However, gender harassment and unwelcome sexual attention were in this sample less common than in an earlier Finnish report using data from an earlier School Health Promotion sample even when response categories 'sometimes' and 'repeatedly' are summarized (Kaltiala-Heino et al, 2016b). Two methodological issues may affect this.…”
Section: Methodological Considerationsmentioning
confidence: 63%
See 1 more Smart Citation
“…Many studies have focused on any experiences in a given time frame (American Association of University Women, 2001;Bucchianeri et al, 2014;Chiodo et al, 2009;Petersen & Hyde, 2009) and therefore focusing on experiences that have occurred 'repeatedly' obviously results in smaller numbers. However, gender harassment and unwelcome sexual attention were in this sample less common than in an earlier Finnish report using data from an earlier School Health Promotion sample even when response categories 'sometimes' and 'repeatedly' are summarized (Kaltiala-Heino et al, 2016b). Two methodological issues may affect this.…”
Section: Methodological Considerationsmentioning
confidence: 63%
“…Sociodemographic variables used were family structure, mother's and father's education, and unemployment in the family. These covariates were used because it has previously been shown that they are associated with experiences of sexual harassment in adolescent population (Kaltiala-Heino et al, 2016, 2016b, and they are also correlates of emotional and behavioral disorders (Hill, 2002;Torikka et al, 2014). The adolescents were asked if they lived with their mother and father together/with mother and father alternately/with mother alone/with father alone/with mother or father and her/his partner/in a foster family/with some other guardian/in a child welfare institution/with some other adult or adults/some other arrangement (clarification requested).…”
Section: Covariatesmentioning
confidence: 99%
“…Subjection to sexual harassment is common among adolescents. In most studies, one to two thirds of adolescents reported to have been subjected to such experiences (Chiodo, Wolfe, Crooks, Hughes, & Jaffe, 2009;Gruber & Fineran, 2007;Kaltiala-Heino, Frojd, & Marttunen, 2016b;McMaster, Connolly, Pepler, & Craig, 2002;Petersen & Hyde, 2009). In a pioneering study in the field of sexual harassment among adolescents (American Association of University Women, 2001), as many as 81% of high school students had reportedly experienced sexual harassment at school.…”
Section: Inrtoductionmentioning
confidence: 99%
“…We hypothesized that an association exists between sexual behavior and experiences of sexual harassment, such that adolescents with more advanced sexual experiences and more intense and risk-taking sexual behavior would also report a greater number of experiences of sexual harassment. Because different types of sexual harassment experiences have similar sociodemographic and mental health correlates (Kaltiala-Heino et al, 2016a, 2016b, we expected that the associations would be similar in all types of sexual harassment. We further hypothesized that these associations would diminish after controlling for confounding due to unfavorable sociodemographic characteristics (not living with both parents, low parental education, parental unemployment) and emotional (depression) and behavioral (delinquency) disorders.…”
Section: The Present Studymentioning
confidence: 99%
“…Sexual harassment is gendered: most studies find that young women are more likely to experience it and young men to perpetrate it. In addition, among those exposed to sexual harassment, young women are more likely than men to find it upsetting [2][3][4][5][6][7]. It should be noted, however, that some studies have found little or no gender differences [8] as well as that the moderating effect of gender on the link between sexual harassment and emotional adjustment may not be consistent [5].…”
Section: Introductionmentioning
confidence: 99%